Infodemic in the First and Second Wave of the Pandemic: Comparative Media Content Analysis of Croatian Portals - Dremel, Anita; Lesinger, Gordana; Jurlina, Juraj (Communication Today, 2022)
In addition to the COVID-19 pandemic since 2020, there has been a pandemic of information, disinformation and fake news connected with it, referred to by the World Health Organisation as an “infodemic”. Taking into consideration that timely, accurate and transparent provision of information is highly relevant in facing health risks, the media worldwide have invested into professional coverage of the topic. However, numerous online communication platforms soon became flooded by incorrect, fabricated and sensationalist information. The aim of this study is to comparatively analyse the infodemic in the context of Croatian web portals (112 texts from 23 web portals) in the first and second wave of the pandemic. Using the method of quantitative media content analysis, two foci were developed in the instrument: one connected with the discourse of/on scientists (3 codes) and the other with iterative thematic analysis (6 codes were used to uncover topics – the source, danger, vaccine, protective masks, distancing, immunity). A Chi-square test was used to test the statistical significance of the difference between the two waves of the pandemic/infodemic. The results suggest there are four statistically significant differences – one related to the first focus (quoting scientists is more frequent in the second wave) and three to the second (the topic of the source of the virus is less present in the texts appearing during the second wave of the pandemic, while topics of immunity and danger are significantly more represented in the second wave).